Clinical Features and Outcomes of Neuropsychiatric Systemic Lupus Erythematosus in China - Shangzhu Zhang; Meng Li; Li Zhang; Ziqian Wang; Qiang Wang; Hui You; Yanhong Wang; Mengtao Li; Xiaofeng Zeng (Journal of Immunology Research)
Objective. To identify the clinical characteristics, magnetic resonance imaging (MRI) results, and prognostic factors of neuropsychiatric (NP) systemic lupus erythematosus (SLE; NPSLE) in a relatively large patient series in China. Methods. Data of patients with NPSLE at Peking Union Medical College Hospital (PUMCH) were collected retrospectively from June 2012 to June 2016. NPSLE patients were compared with 220 non-NPSLE patients. Survival rates were evaluated using the Kaplan-Meier curves, log-rank test, and Cox proportional hazards modeling. Cranial MRI results were also studied. Results. Of the 194 included patients, sixteen subtypes of NPSLE were identified, and the most common manifestations were seizure (36.6%), acute confusional state (25.3%), and cerebral vascular disease (15.5%). Compared with the non-NPSLE group, NPSLE patients were significantly more likely to have typical lupus symptoms, higher Systemic Lupus Erythematosus Disease Activity Index 2000 (SLEDAI-2K) scores (P=0.002), and positive rate of anti-ribosomal P protein antibodies (P=0.008). Patients with seizure were more likely to have higher SLEDAI-2K scores and positive anti-β2GP1 than non-NPSLE patients. Sixteen patients died during follow-up. The most common cause of death was infection (37.5%). NPSLE significantly decreased survival rates of SLE patients. Patients with elevated serum creatinine (P=0.001), hypocomplementemia (P=0.031), and SLEDAI−2K scores≥15 (P=0.014) had shorter survival periods. Eighty-two patients underwent detailed cranial MRI analysis; of these, 50 (61.0%) had abnormal results. Small vessel disease was the most common abnormal finding, followed by inflammatory-like lesions and large vessel disease. Conclusions. High disease activity and positive rate of anti-ribosomal P protein antibodies may be risk factors for NPSLE. NPSLE decreases survival rates of SLE patients. Renal insufficiency and high disease activity are predictive of poor prognoses for NPSLE patients.